Early social communicative skills as predictors of symptom severity in autism spectrum disorder. (November 2017) - Lobban-Shymko, Jan; Im-Bolter, Nancie; Freeman, Nancy
Background and aims: Early diagnosis of autism spectrum disorder, while providing many benefits, also presents challenges. Accurately predicting symptom severity allows clinicians to confidently diagnose and assign the most appropriate intervention. Little available research predicts symptom severity in children with autism spectrum disorder who have not been exposed to significant levels of intervention. Methods: The present file review study examined preverbal skills as predictors of symptom severity, approximately one year later, in a group of young children (18–64 months) with autism spectrum disorder ( n = 199). Results: Of the two core diagnostic features (social communicative deficits and restricted repetitive behaviors), social communicative skills best predicted symptom severity. Furthermore, social communicative gestures predicted symptom severity after age, adaptive behavior, restricted repetitive behaviors, and functional gestures had been accounted for. Conclusions: Social communicative gestures are excellent predictors of future symptom severity independent of intervention effects in very young children with autism spectrum disorder. Implications: Previously, the social aspect of gestures has been missing in the literature on language and symptom prediction in children with autism spectrum disorder. Careful attention to social communicative gestures in the future may help with early diagnosis and more accurate predictions of symptom and developmental trajectories.